ACTUAL PROBLEMS OF AUTOMATION OF TECHNOLOGICAL PROCESSES AND PRODUCTION AND APPLICATION OF FUZZY LOGIC AS A SOLUTION - Ibragimov Islomnur; Ibragimov Begobod Sheraliyevich (Galaxy International Interdisciplinary Research Journal, 2023)
This article examines the automated control model of the production of construction materials, which provides an opportunity to obtain the optimal structure based on the criterion of reliability.